Emotional responses to a dynamite attempt - Forero Pulido, Constanza; Pérez P., Liria; Anduquia V., Paula Andrea; Flórez B., Alex (Investigación y Educación en Enfermería, 2008)
In the year 2001 in Lleras Park, Medellín, Colombia, a terrorist dynamite explosion occurred, dammaging buildings. Many people were injured as well. This article deals with the descriptive and retroactive study about the effects of the blast in the buildings, the injuries and the psycho-affective emotions of the affected persons. This article was prepared bearing in mind the psycho-affective emotions of the affected persons. It deals with the analysis of the deepest feelings of the injured and affected people regarding the repercussions of that incident in their lives and it embodies an educational proposal providing professional nurses with elements for the care of individuals and groups that live in risky conditions or that have endured terrorist acts. In social literature ";psycho-affective emotions"; is becoming a more frequent term and it has nothing in common with ";desequilibrium"; or ";disharmony";. From this perspective the more evident and common emotions of the survivors were analysed Key Words: wounds and injuries, explosion trauma, emotional disorder, fear, stress, hate, Medellín